Sensing electrode inhomogeneity and electrochemical heterogeneity using an electrochemically integrated multielectrode array - Tan, Yong-jun (The Electrochemical Society ECS, 2009)
This paper provides a brief review of the wire beam electrode WBE and its applications in measuring, characterizing, and evaluating surface inhomogeneity and electrochemical heterogeneity. The WBE is a unique multielectrode array that is electrochemically integrated by coupling all electrode terminals together and by closely packing all electrodes. A WBE surface typically consists of 100 nominally identical and individually addressable electrodes that effectively mimic a conventional single electrode in electrochemical behavior. Pre-existing surface inhomogeneity can be analyzed by detecting electrochemical parameters from various locations over a WBE surface. Electrochemical integration of the WBE working surface permits electrochemical heterogeneity to evolve dynamically and propagate freely. Typical experiments are presented to illustrate the applications of the WBE indetecting electrode inhomogeneity, in sensing localized corrosion, in measuring electroplating, and in monitoring anodic dissolution and polymerization.